Biomedical Applications of Supramolecular Materials in the Controllable Delivery of Steroids - Hao, Yun; Zhang, Feiyi; Mo, Shanshan; Zhao, Jinming; Wang, Xiangdong; Zhao, Yan; Zhang, Luo (Frontiers in Molecular Biosciences, 2021)
Glucocorticoids are a class of steroid hormones secreted from the adrenal glands. The strong anti-inflammatory effects make it be one of the most popular and versatile drugs available to treat chronic inflammatory diseases. Additionally, supramolecular materials have been widely exploited in drug delivery, due to their biocompatibility, tunability, and predictability. Thus, steroid-based supramolecular materials and the release of steroids have been applied in the treatment of inflammatory diseases. This mini-review summarized recent advances in supramolecular materials loaded with glucocorticoid drugs in terms of hydrophobic interactions, electrostatic interactions, hydrogen bonding, and π-π stackings. We also discussed and prospected the application of the glucocorticoid drugs-based supramolecular system on chronic rhinosinusitis, multifactorial inflammatory disease of the nasal and paranasal sinuses mucosal membranes. Overall, supramolecular materials can provide an alternative to traditional materials as a novel delivery platform in clinical practice.